A network pharmacology-based approach and molecular docking study to explore the therapeutic potential of a nutraceutical formula (Vernolac) in the treatment of cancer - Sandani De Vass Gunawardane; Matheen Muhammadh Milhan; Poorni Chanuka Rathnayake; Prabudhi S. Garusinghe; Kavishka S. Gunaratne; Anusha Kanagasundaram; T. M. D. Darshanamala; Duvinika Chalani Senevirathne; Shalini Kaushalya Wijerathne; R. P. C. D. Perera; Kanishka Sithira Senathilake; Umapriyatharshini Rajagopalan; et al. (PLoS ONE, 2026)
Vernolac is a commercially available polyherbal nutraceutical capsule containing Vernonia zeylanica aerial parts, Nigella sativa seeds, Hemidesmus indicus roots, Leucas zeylanica aerial parts, and Smilax glabra rhizome. Herbal formulations, organic extracts, and isolated phytochemicals from these plants have demonstrated anticancer properties. However, the mechanisms underlying Vernolac’s anticancer activity as a polyherbal formulation remain largely unexplored. This study utilized an integrative network pharmacology-based approach, supported by in vitro experiments, to investigate Vernolac’s anticancer potential. Phytochemicals were retrieved from databases, screened for drug-likeness and oral bioavailability using SwissADME, yielding 155 drug-like compounds, and their protein targets were predicted using SwissTargetPrediction. The intersection of phytochemical targets with cancer-related targets from GeneCards identified 137 common targets. Protein-protein interaction analysis using STRING and Cytoscape revealed fourteen key hub nodes, including AKT1, BCL2, CASP3, CTNNB1, EGFR, ESR1, GAPDH, HSP90AA1, HSP90AB1, IL6, JUN, SRC, STAT3, and TNF. Network analyses highlighted key phytochemicals, including vernolactone, thymoquinone, quercetin, nigellidine, α-hederin, and carvacrol. GC–MS profiling of the supercritical CO 2 extract of Vernolac revealed a diverse phytochemical composition enriched with terpenes, fatty acids, and sterols, including the key constituents stigmasterol, thymoquinone, and carvacrol. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed significant enrichment of the identified targets across multiple cancer pathways. Molecular docking and dynamics simulations identified novel target-ligand interactions, such as vernolactone-β-catenin and α-hederin-CDK4. The Sulforhodamine B assay demonstrated selective antiproliferative activity of Vernolac extract against cancerous cell lines MCF-7 (IC 50 = 54.01 ± 0.02 μg/mL), Caco-2 (IC 50 = 85.52 ± 0.13 μg/mL), NTERA-2 cl.D1 (IC 50 = 42.41 ± 0.06 μg/mL), and non-cancerous MCF-10A (IC 50 = 803.5 ± 0.03 μg/mL). Collectively, network analysis suggests that phytochemicals in Vernolac may exert anticancer effects through multiple cancer-related pathways, including those associated with apoptosis, immune modulation, oxidative stress, inflammation, and cell proliferation. Furthermore, the identified targets and enriched pathways suggest a potential role in modulating drug resistance and treatment response, providing a computational basis for its application as an adjunct to conventional cancer therapies and warranting further investigation in preclinical and clinical settings.